Coping skills interventions for children and adolescents - Forman, Susan G. (Jossey-Bass social and behavioral science series, 1993)
Children and adolescents encounter a variety of potentially stressful situations on a daily basis. In this book, Susan G. Forman provides school psychologists, counselors, social workers, and teachers with a wide range of coping skills interventions designed to help them teach children how to handle stress and deal more competently with academic, interpersonal, and physical demands both in and out of the classroom. In addition to covering the historical development of each intervention, Forman also details the specific techniques that can be used to promote and evaluate student change. She shows how instruction in relaxation techniques, social problem-solving skills, and assertiveness skills can promote the growth of interpersonal and emotional competence. And she discusses the key factors in successful implementation, such as winning support from a number of different sources and monitoring and evaluating the effectiveness of intervention programs. From teaching students the use of verbal self-instruction to applying the principles of rational-emotive therapy to help construct new patterns of thinking, Forman reveals how coping skills interventions can help young people develop into healthy, competent adults.